Purification, Characterization, And Microemulsion Spray Formulation Of Enterocin Secreted By Enterococcus Faeciumcc2 Against Oral Pathogen Streptococcus Mutansukmcc 1019 - Ng, Zhang Jin (2023)
Dental caries is the most common noncommunicable disease worldwide and Streptococcus mutans is the main oral pathogen which contributes to it. Using of chlorhexidine mouthwash in the inhibition of S. mutans may cause some side effects to human beings and also harmful to aquatic life. Bacteriocin-like inhibitory substance (BLIS) from lactic acid bacteria can be the replacement for chlorhexidine in the inhibition of S. mutans. In this study, out of the 61 LAB strains, the BLIS produced by Enterococcus faecium CC2 showed highest inhibition activity against S. mutans UKMCC 1019. BLIS produced by E. faecium CC2 have high tolerance to acidic, alkaline and high temperature environment. It is a proteinaceous nature substance that possess of 4406.655 AU/mL and 268.592 AU/mL inhibition activity against S. mutans UKMCC 1019 and Candida albicans, respectively. Under TEM, cell lysis of S. mutans UKMCC 1019 was observed. Partial purification of BLIS was done by ammonium sulphate precipitation, following by ionic liquid based aqueous two-phase system (ILATPS) and polyethylene glycol (PEG) based aqueous two-phase system (ATPS), respectively. The highest purification factor, recovery yield and partition coefficient achieved from PEG based ATPS were higher than ILATPS.